Use of Image Data in Kinetic Model Development for the Design of Mesenchymal Stem Cell Cultivation Processes - Hirono, Keita; Hayashi, Yusuke; Udugama, Isuru A.; Takemoto, Yuto; Kato, Ryuji; Kino-oka, Masahiro; Sugiyama, Hirokazu (Computer Aided Chemical Engineering, 2024)
This work presents the use of image data in kinetic model development for designing mesenchymal stem cell (MSC) cultivation processes. To incorporate the initial spatial distribution of seeded cells, seeding bias in static MSC cultivation was investigated with phase contrast microscopic image acquisition on Day 1. Subsequently, a parameter was newly defined from the image analysis result calculating the standard deviation of cell number fraction among numerical 64 tiles on a squared culture space. Finally, the parameter was integrated with our previous kinetic model to consider spatial growth limitation. The model was then applied to simulate static MSC cultivation processes. Based on ordinary differential equations (ODE), Monte-Carlo simulations were conducted to find cell harvesting time when cultivation ensured given specifications for cell number and confluence degree. Feasible range of harvesting time was illustrated subject to seeding heterogeneity and density. The presented image-based ODE model could help incorporate spatial heterogeneity into the MSC cultivation process design.